Genetic Diversity of Red Snapper (Lutjanus erythropterus) in Kaimana Waters - Milansari, Sindi; Toha, Abdul Hamid A.; Pranata, Bayu; Dailami, Muhammad; Manangkalangi, Emmanuel; Jeni, Jeni (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Genetic diversity is one level of biodiversity that is very importan for the resilience of biota in the face of environmental pressures such as cilmater change. However, information on the genetic diversity of red snapper in Kaimana water is still very limited. This study determines the genetic diversity of red snapper (Lutjanus erythropterus) in Kaimana waters, West Papua, to support conservation and sustainable management. The methods used include PCR, DNA sequencing, and phylogenetic analysis using MEGA11, with samples taken from the Kaimana fish market. The results of this study show differences in the percentage of adenine and guanine in sample B81.01, with an average codon composition of 218 codons, where UCU(G) Serine has the highest percentage of 13.8% and RSCU 2.38%, and 20 types of amino acids were detected. Lutjanus erythropterus has 3 haplotypes, with 2 universal haplotypes and 1 specific. In Kaimana waters, the haplotype diversity (hd) value is 0.50000 and the nucleotide diversity (π) is 0.00091, which is influenced by the large population size and high migration ability.